2008
DOI: 10.1097/01.nne.0000299494.38367.5e
|View full text |Cite
|
Sign up to set email alerts
|

Are We Moving Toward an Expanded Role for Part-time Faculty?

Abstract: The 30-year trend of increased use of part-time faculty in higher education warrants the following questions: Are part-time faculty roles changing in light of the increased presence of part-time faculty in the academia? In addition, what is their contribution to the educational institution's mission of research, teaching, and service? Boyer's model of scholarship was used in this research to answer these questions. The author discusses the research findings and their implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Schools of nursing innovatively utilize adjunct faculty to fill the gap experienced from increased student enrollments and lack of qualified full-time nursing faculty. Within nursing education, the majority of adjunct nurse faculty members are hired to teach in the clinical role and are essential to fill changing course loads each semester delivered at a cost savings (Caruth & Caruth, 2013;Creech, 2008;Duffy, Stuart, & Smith, 2008). Despite the importance of adjunct faculty, barriers exist to job satisfaction and intent to stay in the teaching role.…”
Section: The Problem and Domain Of Inquirymentioning
confidence: 99%
See 2 more Smart Citations
“…Schools of nursing innovatively utilize adjunct faculty to fill the gap experienced from increased student enrollments and lack of qualified full-time nursing faculty. Within nursing education, the majority of adjunct nurse faculty members are hired to teach in the clinical role and are essential to fill changing course loads each semester delivered at a cost savings (Caruth & Caruth, 2013;Creech, 2008;Duffy, Stuart, & Smith, 2008). Despite the importance of adjunct faculty, barriers exist to job satisfaction and intent to stay in the teaching role.…”
Section: The Problem and Domain Of Inquirymentioning
confidence: 99%
“…Faculty can fulfill teaching roles in the didactic (traditional classroom and online), laboratory, and/or clinical settings. Schools of nursing report the clinical setting as the largest unfilled faculty need and most notably staffed by adjunct faculty (Creech, 2008;Duffy et al, 2008;Forbes, Hickey, & White, 2010;Koharchik, 2014;Peters & Boylston, 2006;Roberts & Glod, 2013;Santisteban & Egues, 2014;West, 2010). The significant need for clinical teaching is attributed to structured limitations for clinical learning set by state boards of nursing or individual schools of nursing with teacher to student ratios of 1:8 to 1:12 (Caton, Conner, DeWitt, Jones, & Stubbs, 2007;Dickson, Walker, & Bourgeois, 2006;Teel, 2008;West et al, 2009).…”
Section: The Clinical Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Of late, general use of adjunct faculty within all colleges and universities was about 73% of the total faculty (Stainburn, ). Employing adjunct faculty serves nursing programs by (a) decreasing financial expenditures associated with exclusively employing full‐time faculty, (b) increasing flexibility in didactic course and clinical offerings, and (c) compensating for unfilled full‐time faculty positions across educational settings (Creech, ). Yet, while adjunct faculty may successfully meet some of the challenges faced by nursing programs, they themselves face many challenges hindering their success as nurse educators.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…There has been a substantial increase in the number of part‐time faculty in baccalaureate nursing programs. Part‐time nursing faculty increased by 17% from 1996 to 2002, while full‐time faculty grew by only 10%, reaching almost 50% of educators (Creech, ). A study on nursing faculty in the old Carnegie Foundation I and II classifications universities found that, contrary to the belief that part‐time nursing faculty were not an integral part of the educational endeavor, they have a broader scope of responsibility for the teaching and service mission than commonly thought (Creech, ).…”
Section: Recent Changes In Nursing Education In Higher Educationmentioning
confidence: 99%